2019
DOI: 10.1177/1359105319845130
|View full text |Cite
|
Sign up to set email alerts
|

It’s all relative: Increasing organ donor registration intentions by maximizing family-relevant vested interest

Abstract: Guided by vested interest theory, the impact of educating potential organ donors about the beneficial experiences afforded to families of deceased donors was assessed. Participants were informed about these benefits by taking a survey that asked them to indicate both their awareness, and the appeal, of numerous existing benefits (e.g. grief services). We employed a double-sided mixed design. Both the true experimental design and the quasi-experimental repeated assessment indicated increased registration intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…As noted, scholars rarely have assessed the potential of focusing interventions on the broad range of benefits to the family; however, previously conducted studies highlight the potential of this approach. For example, Siegel and colleagues (2021) conducted an experimental study that informed participants of a large range of benefits afforded to donor families. Participants reported higher levels of registration intentions compared to a control condition.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As noted, scholars rarely have assessed the potential of focusing interventions on the broad range of benefits to the family; however, previously conducted studies highlight the potential of this approach. For example, Siegel and colleagues (2021) conducted an experimental study that informed participants of a large range of benefits afforded to donor families. Participants reported higher levels of registration intentions compared to a control condition.…”
Section: Discussionmentioning
confidence: 99%
“…The messages were not pilot tested, but the efficacy and altruism messages mirrored language from a prior intervention (Siegel, Alvaro, Crano, et al, 2008) and are in line with messaging commonly found on donor websites (www.organdonor.gov). The vested interest messaging was derived from focus groups conducted for this project and a survey of nondonors focused on the family benefits perceived as most important (Siegel et al, 2021). The control condition did not have any donor-specific content.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations